2009
DOI: 10.1021/om900299k
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reaction of Mo(CO)6 with Et2GeH2: NMR and DFT Studies of Reaction Products; Crystal Structure of a Novel Complex [{Mo(μ-η2-H−GeEt2)(CO)4}2]

Abstract: The photochemical reaction of Mo(CO) 6 with the diethylgermane Et 2 GeH 2 leads to the formation of several new complexes, which were detected by IR and 1 H and 13 C NMR spectroscopy. From the mixture of compounds, a binuclear complex, [{Mo(μ-η 2 -H-GeEt 2 )(CO) 4 } 2 ], was isolated in crystalline form, and its molecular structure was established by single-crystal X-ray diffraction studies. The agostic hydride ligand of the Mo( μ-η 2 -H-GeEt 2 ) group was located in the structure at a chemically reasonable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…All calculations have been performed utilizing the PBE0 [37][38][39] exchange-correlation functional of density functional theory and the 6-311G(d,p) basis set [40,41]. It was shown that PBE0 gives reasonable molecular structures [12,42] as well as electronic densities [43,44]. On the other hand, the 6-311G(d,p) basis set is of valence triple zeta quality and, additionally, includes polarization functions for all atoms.…”
Section: Computational Methodologymentioning
confidence: 99%
“…All calculations have been performed utilizing the PBE0 [37][38][39] exchange-correlation functional of density functional theory and the 6-311G(d,p) basis set [40,41]. It was shown that PBE0 gives reasonable molecular structures [12,42] as well as electronic densities [43,44]. On the other hand, the 6-311G(d,p) basis set is of valence triple zeta quality and, additionally, includes polarization functions for all atoms.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Overall, the structure of the GeH 2 adduct 5 is similar to its tin congener 4 (Fig. S4, ESIw), with a canted transoid arrangement of the C(7)-C(6)-Ge-W unit [torsion angle = 146.45 (14) 17 and IPrÁGeH 2 ÁBH 3 [2.011(2) A ˚]. 3 The proximal C(6)-C(7) bond length was 1.463(3) A ˚and lies within the range expected for a C-C single bond; as in 4, the endocyclic C(7) center in the Ge adduct was planar [angle sum = 360.0(3)1].…”
Section: ð2þ ð3þmentioning
confidence: 99%
“…Recently, the ability of photochemically generated coordinatively unsaturated carbonyl complexes of molybdenum(0) to activate the Ge-H -bond of germanes has been discovered and taken advantage of in the hydrogermylation of norbornadiene [80,81]. In photochemical reaction of Mo(CO) 6 , [Mo(CO) 4 (nbd)], or [Mo(CO) 4 (cod)] with Et 3 GeH, the 2 -coordination of the Ge-H bond to the molybdenum atom was detected by 1 H NMR spectra, due to characteristic high-field resonance in the region from -6 to -8 ppm.…”
Section: Hydrogermylation Of Alkenesmentioning
confidence: 99%
“…Carbonyl complexes of molybdenum are of great utility owing to their applications as precursors for the generation of true catalysts for such reactions as metathesis , metathesis polymerization and oligomerization [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], radical reactions [57][58][59][60][61][62][63][64][65], hydrogenation [66][67][68][69][70][71][72][73][74], hydrosilylation [75][76][77][78][79], hydrogermylation [80,81], hydrostannation [82][83][84][85][86][87]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation